Comparative Phospho- and Acetyl Proteomics Analysis of Posttranslational Modifications Regulating Intestine Regeneration in Sea Cucumbers - Sun, Lina; Lin, Chenggang; Li, Xiaoni; Xing, Lili; Huo, Da; Sun, Jingchun; Zhang, Libin; Yang, Hongsheng (Frontiers in Physiology, 2018)
Sea cucumbers exposed to stressful circumstances eviscerate most internal organs, and then regenerate them rapidly under favourable environments. Reversible protein phosphorylation and acetylation are major modifications regulating protein function. Herein, for the first time, we perform quantitative phospho- and acetyl proteomics analyses of intestine regeneration in a sea cucumber species Apostichopus japonicus. We identified 1,862 phosphorylation sites in 1,169 proteins, and 712 acetylation sites in 470 proteins. Of the 147 and 251 proteins differentially modified by phosphorylation and acetylation, respectively, most were related to cytoskeleton biogenesis, protein synthesis and modification, signal recognition and transduction, energy production and conversion, or substance transport and metabolism. Phosphorylation appears to play a more important role in signal recognition and transduction than acetylation, while acetylation is of greater importance in posttranslational modification, protein turnover, chaperones; energy production and conversion; amino acid and lipid transport and metabolism. These results expanded our understanding of the regulatory mechanisms of posttranslational modiﬁcations in intestine regeneration of sea cucumbers after evisceration.